Molecular structures of some bivalent metal complexes of 1-(4-acetylphenyl)imidazole and co-ligands. (15th July 2018) - Behera, Nibedita; Manivannan, Vadivelu
Graphical abstract: Metal complexes of 1-(4-acetylphenyl)imidazole along with the coligands show different supramolecular architectures through the weak interactions; OH⋯O, CH⋯O, CH⋯Cl, CH⋯π, π⋯π interactions. Fumarate ion coordinate to metal centers Co(II) and Mn(II) in bidentate and tetradentate fashions respectively and form 1D and 2D coordination polymers. Abstract: A series of bivalent metal complexes having compositions [Co(L )2 Cl2 ] (1 ), [Zn(L )2 Cl2 ] (2 ), [Co(L )2 (H2 O)4 ](NO3 )2 ·2H2 O (3 ), [Zn(L )2 (H2 O)4 ](NO3 )2 ·2H2 O (4 ), [Co(L )2 (OAc)2 (H2 O)]·3H2 O (5 ), [Mn(L )2 (OAc)2 (H2 O)]·3H2 O (6 ) [Co(L )4 (NCS)2 ] (7 ), {[Co(L )2 (Fum )(H2 O)2 ]·2H2 O} n (8 ) and {[Mn(L )2 (Fum )]} n (9 ) were synthesized using L {L  = 1-(4-acetylphenyl)imidazole} and respective co-ligands. The mononuclear sets 1 –2, 3 –4 and 5 –6 are isomorphous and isostructural in nature. Complex 7 is a mononuclear complex, 8 is a 1D coordination polymer and 9 is a 2D-coordination polymer. All the compounds were structurally characterized using IR spectroscopy, thermogravimetric analyses, powder X-ray and single crystal X-ray diffraction studies. In general, coordinated/lattice water molecules are found to be involved in OH⋯O hydrogen bonding and counter ions, in other weak interactions like CH⋯S, CH⋯Cl and CH⋯O. The aromatic ring of L also is involved in CH⋯π and π⋯π stacking interactions. In 3 and 4, hydrogen bonding interactions between coordinated water molecules, lattice water and nitrate ion contain cyclic hydrogen-bonded architectures. In 5 and 6, acetyl group present in L act as hydrogen bond acceptor through O⋯HO interaction. In 8 and 9 Fum coordinate to metal center in μ-η 1 :η 1 bidentate and μ4 -η 1 :η 1 :η 1 :η 1 tetradentate fashions resulting in formation of 1D and 2D coordination polymers, respectively.